Urine Metabolite Risk Factors of DJ Stent’s Biofilm Formation in Patients with Urinary Tract Stones - Besut Daryanto; Muhammad Miftahul Firdaus (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2020)
Introduction: Since first introduced by Finney and Hepperlen in 1978, the Double-J